Prosedur Pendaftaran Tanah Adat Secara Sporadik dan Perlindungan Hukum Pemilik Tanah Beritikad Baik - Cornelia, Anita; Dewi Saraswati, Mutiara; Falyafil, Zakaria; Husein, Kamal (UNES Law Review, 2023)
The implementation of land registration for the first time contained various problems, refer to State Administrative Court Decision Number 81/G/2012/PTUN-MDN jo. Decision of the High State Administrative Court Number 73/B/2013/PT.TUN-MDN jo. Supreme Court Decision Number 457K/TUN/2013 in conjunction with Supreme Court Decision Number 77 PK/TUN/2015, where the land belonging to Che'Dah is traditional Grant land used by Mario Lumban Tobing and sold to Christian Radjagukguk with the approval of Che'Dah, Christian Radjagukguk sold the house building to Saminah Br. Tampubalon, but the land has been issued a certificate of ownership rights number 327, Sukaraja sub-district by Datuk Syarial who obtained through conversion the recognition of rights and Datuk Syarial is the heir of the late Datuk Kamal. This research will find the answers to a problem, the type of research used is normative juridical which refers to laws and regulations that are passed and in force in Indonesia. The conclusion of this research is that the issuance of KTUN in the form of SHM Number 327/Sukaraja in the name of Datuk Syahrial is not in accordance with land registration procedures for the first time as stated in Article 12 paragraph (1) of GR Number 24 of 1997 and violates the GCG because it has harmed Norma Tampubalon as controller of the land acted in good faith. Ownership of land in good faith for 20 consecutive years is entitled to legal protection for sporadic land registration by unauthorized parties in the form of cancellation of SHM Number 327/Sukaraja. Cancellation of KTUN in the form of SHM can be done in 3 ways, namely requesting cancellation from the Minister of ATR/BPN through the Land Office, filing a lawsuit at the State Administrative Court (PTUN), or filing a lawsuit at the district court on the basis of an unlawful act.